2014
DOI: 10.21101/cejph.a3947
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking during Pregnancy and Birth Outcomes in a Sample of Romanian Women

Abstract: SUMMARYSmoking during pregnancy is causally associated with reduced birth weight and is strongly related to preterm birth. Smoking cessation in early pregnancy seems to reduce these risks, although the research evidence is limited. In a sample of Romanian women, differences in birth outcomes were assessed between non-smokers and women who continued to smoke during pregnancy and non-smokers and women who stopped smoking when they found out about the pregnancy. Pregnant women were recruited in two urban clinics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Though the figure was lower, active or passive tobacco smoke exposure during pregnancy has adverse health effects on the fetus, as well as the mother. The adverse health effect of cigarette smoke on the fetus includes, an increased risk of strabismus in the offspring [71], clubfoot [72], low birth weight for gestational age (LBWGA), low birth weight, preterm births (28,29), increased odds of elevated levels of antisocial behaviors during adolescence and adulthood, as well as violent and nonviolent outcomes [73], an increased risk of wheeze in children [74], and almost 3 times increased risk of congenital heart defects [75]. Moreover, tobacco smoke during pregnancy increases the prevalence of depressive symptoms during pregnancy [76].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Though the figure was lower, active or passive tobacco smoke exposure during pregnancy has adverse health effects on the fetus, as well as the mother. The adverse health effect of cigarette smoke on the fetus includes, an increased risk of strabismus in the offspring [71], clubfoot [72], low birth weight for gestational age (LBWGA), low birth weight, preterm births (28,29), increased odds of elevated levels of antisocial behaviors during adolescence and adulthood, as well as violent and nonviolent outcomes [73], an increased risk of wheeze in children [74], and almost 3 times increased risk of congenital heart defects [75]. Moreover, tobacco smoke during pregnancy increases the prevalence of depressive symptoms during pregnancy [76].…”
Section: Plos Onementioning
confidence: 99%
“…Different chemicals from cigarette smoking impair the structure and function of the placenta [27]. Therefore, smoking during pregnancy has been associated with preterm birth, restricted fetal growth and low birth weight [28,29], and this leads to a higher risk of childhood obesity and non-communicable diseases in later life [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing pregnant self-reports on smoking status, our study showed a high frequency of women who smoked before pregnancy (30.04%) of which a high percentage (43.3%) continued to smoke during pregnancy, a high frequency even for Romania [22,23,24].…”
Section: Discussionmentioning
confidence: 91%
“…The recent smoking cessation approaches tend to focus on this chronic, relapsing dependence on tobacco, even by monitoring components of nicotine in the blood, or sa- liva. The success of such approach involves understanding of the chronic nature of tobacco addiction, the monitoring period (not just interventions in the acute stages of manifestation) associated with behavioral educating both for healthcare professionals and also for pacients [20,23]. We believe that the results of this study will enable a shift in starting up community interventions more effective in smoking cessation outcomes, manifest especially among young women who are pregnant or are preparing to be, from different ethnicities and specific socio-demographic and cultural profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The other important aspect of this study is an integrated approach to the entirety of factors women are exposed to expressed with the help of statistical methods adapted for the solution of a specific problem. In the literature sources, the attempts to develop systems for the prediction of preterm labour can be found, however they failed to be put in practice due to complexity or failure to include sufficient number of factors [4,6,14,17]. Having studied the impact of independent factors on preterm labour we present the equation, which rather exactly describes the preterm labour risk and can be easily applied by the physicians in their practice.…”
Section: Discussionmentioning
confidence: 99%